In search of Balkania : A Users' Manual - Neue Galerie am Landesmuseum Joanneum, Graz; Abramovic, Velimir; Benjamin, Walter; Beros, Nada; Bjelic, Dusan; Boubnova, Iara; Boyadjiev, Luchezar; Boyadyievska, Maja; Bratescu, Geta; Celac, Mariana; Conover, Roger; Cufer, Eda; et al. (Graz : Neue Galerie am Landesmuseum Joanneum Graz, 2002)
Abramovic, Marina ; Adzievski, Tome ; Alptekin, Hüseyin ; Altindere, Halil ; Asal, Selda ; Bogdanov, Georgi ; Boyadjiev, Luchezar ; Bratescu, Geta ; Celac Király Marcu ; Cvjetanovic, Boris ; Delimar, Vlasta ; Dimitrijevic, Braco ; Dordevic, Goran ; Eclipse ; Ersen, Esra ; Gemisheva, Mariela ; Gotovac, Tomislav ; Graur, Teodor ; Grigorescu, Ion ; Hazifejzovic, Jusuf ; Ioan, Augustin ; IRWIN ; Ivekovic, Sanja ; Karamustafa, Gülsün ; Keser, Ivana ; Kovacevic, Milomir ; Kurt & Plasto ; Kyriakakos, Athanasia ; Leko, Kristina ; Malevich, Kasimir ; Mangelos ; Margineanu, Nicolae ; Martek, Vlado ; Matic, Goranka ; Missirkov, Boris ; Moudov, Ivan ; Murtezaoglu, Aydan ; Naskovski, Zoran ; Oroveanu, Mihai ; Ostojic, Tanja ; Paci, Adrian ; Papadimitriou, Maria ; Peljhan, Marko ; Prashkov, Kiril ; Sala, Anri ; Sarkanjac, Branislav ; Serapionov, Kalin ; Shkololli, Erzen ; Soba, Nebojsa seric ; Solakov, Nedko ; Solomon, Alexandru ; Stankovski, Aleksandar ; Stilinovic, Mladen ; SubREAL ; Svetieva, Aneta ; Todosijevic, Rasa Dragoljub ; Tomic, Milica ; Vangeli, Zaneta ; Vekic, Dejan
geboortedatum per kunstenaar
Engels
In Search of Balkania, Neue Galerie am Landesmuseum Joanneum Graz, 5.10.2002 - 01.12.2002
boek
Keywords: Balkan